Islamic Justice In A Monetary System: A Modest Proposal (American Journal of Islam and Society, 1987)
Dr. M. Umer Chapra. Towards a Just Monetary System. Leicester:The Islamic Foundation. 1985. 292p.Extensive literature on the institutional aspects of monetary economics includespioneering studies by Muhammad Uzair, Muhammad Nejatullah Siddiqi,Ziauddin Ahmed, Anwar Iqbal Qureshi, Afzalur Rahman, and theCouncil of Islamic Ideology in Pakistan among many others. Scores ofresearch papers have elaborated the functioning of Islamic banking in theoryand practice. A fresh study on Islamic banking in Iran and Pakistan by ZubairIqbal and Abbass Mirakhor has been released by the International MonetaryFund. In the voluminous literature on issues dealing with money and bankingin Islam, Towards Q Just Monetary System is outstanding in many respects.The study is tightly knit, thoroughly documented, and the ideas are carekllyanalyzed. These qualities are lacking in most works on Islamic economics.Competence in ecnomics and command of Arabic for access to originalsources in Islam is essential for a scholarly integration of shari'ah and modemeconomic analysis in order to address ContempOrary economic problems.There is no doubt that Dr. Umer Chapra, Economic Adviser to the Saudi ArabianMonetary Agency, has all the necessary background.Towards a Just Monetary System introduces a perspective on the interestbearingsystem before outlining various socio-economic goals and strategiesin chapter one. Islamic views on the nature of riba are discussed in chaptertwo supported by a comprehensive appendix based on the Qur'an, Ahadith,and Fiqh literature on riba. Equity-based financing as an alternative tointerest-based financing is proposed in chapter three, for which necessaryreforms are outlined in chapter four. A vigorous comparison is drawn inchapter five between interest-bearing and interest-free systems in terms ofallocation of resources, saving and capital formation, stability, economicgrowth, and fulfilment of various types of credit needs. Some necessary ...